Optimization of Alkaline Pretreatment and Fermentation Conditions for Improved Physicochemical Properties and Yield of Bioethanol Produced from Sugarcane Bagasse - Bosede A. ORHEVBA; Sodeeq A. OLAJIDE (FUDMA Journal of Engineering and Technology, 2025)
Selected processing parameters were optimized to determine their impact on the yield and some physicochemical properties of bioethanol derived from sugar cane (Saccharum officinarum) bagasse. Bioethanol was produced from sugar cane bagasse using alkaline pretreatment method, simultaneous saccharification and fermentation processes. The physicochemical properties determined were: Density,  kinematic viscosity, specific gravity, boiling point, pour point, pH value and ethanol concentration. The analytical methods used followed standard procedures. Two-way factor was used for the  analysis of variance (ANOVA) to evaluate the effect of these processing parameters on the yield and physicochemical properties. The results revealed that the processing methods (alkaline pretreatment method, simultaneous saccharification and fermentation processes), had significant effect (p
Keywords: Bioethanol, sugarcane bagasse, simultaneous saccharification, alkaline pretreatment, fermentation process.